2015
DOI: 10.1182/blood-2014-11-610824
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role for the VWF A1 domain in binding to type IV collagen

Abstract: • Collagen 4 binds to the VWF A1 domain, and this binding is reduced or abrogated by select VWF A1 domain sequence variations.• Platelet binding to collagen 4 under flow conditions is dependent on the presence of VWF.Von Willebrand factor (VWF) contains binding sites for platelets and for vascular collagens to facilitate clot formation at sites of injury. Although previous work has shown that VWF can bind type IV collagen (collagen 4), little characterization of this interaction has been performed. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 35 publications
2
85
0
Order By: Relevance
“…Differences in collagen binding were observed as previously reported. 19 At the time of initiation of this study, type 2M did not routinely include collagen-binding variants, so these subjects remained in the type 1 cohort for this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences in collagen binding were observed as previously reported. 19 At the time of initiation of this study, type 2M did not routinely include collagen-binding variants, so these subjects remained in the type 1 cohort for this study.…”
Section: Resultsmentioning
confidence: 99%
“…Our data showed that subjects with laboratory findings otherwise consistent with type 1 VWD but with low VWF:CB4 had increased bleeding symptoms as measured by BS. 19 Although only 12 subjects were affected, this represented 4% of type 1 subjects. This raises the possibility that these subjects may be better classified as type 2M VWD on the basis of a functional defect in the VWF protein, even though the VWF:RCo/VWF:Ag ratio was normal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the majority of mutations are located in the A3 domain, and exons 29-32 should be investigated. A small proportion of A1 domain mutations result from collagen types IV or VI binding defects [34].…”
Section: Molecular Characterization Of Type 1 and 3 Vwd Patientsmentioning
confidence: 99%